Aedes sp Density Analysis as an Evaluation of PSN-DBD on Primary Purwokerto Year 2013 - Arif Widiyanto; Agus Subagiyo; Listyaning Eko Martanti (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2014)
PSN- DBD is the method to reduce mosquito's larva breeding sources, which is a vital strategy for preventing Dengue Hemorrhagic Fever (DHF). Active public participation is required to implement PSN- DBD. Community is not only regarded as an object, but also as the subject or perpetrator. The main targets of the PSN - DBD is all families; communities; schools; and public places, including industrial areas. These targets are expected to perform PSN - DBD by eliminating mosquito breeding places and maintaining healthy environment in their homes and respective communities on an ongoing basis. The purpose of this study was to determine container index and describe the implementation of PSN - DBD on elementary environments in Purwokerto. The descriptive method was used to survey eight elementary schools in Eastern, Western, Norhtern, and Southern districts of Purwokerto. The study was conducted by counting the larvae of Aedes sp to identify container index in tubs, water containers and containers of water for ritual wash. Findings revealed container index of 25 % at SDN 1 Bantarsoka and SDN 1 Karang Klesem, while container index of other elementary schools was 0%. PSN - DBD had been implemented in all elementary, except at SDN 1 Bantarsoka and SDN 1 Karang Klesem. Efforts to clean the tubs and drainage systems had not been carried out regularly for at least once a week. The schools should pay an active role in blocking the chains of the disease's transmission through PSN-3M activities, which included cleaning water containers and drainage systems, burying ground surface/ destroying potential mosquito breeding sites, and closing the water reservoirs. In addition, schools should always maintain good environmental school hygiene.